Muscle Oxygenation and Blood Volume Reliability during Continuous and Intermittent Running - Ihsan, M.; Abbiss, C. R.; Lipski, M.; Buchheit, M.; Watson, G. (International Journal of Sports Medicine, 2013)
The reliability of near infrared spectroscopy derived tissue oxygenation index (TOI) and total haemoglobin concentration (tHb) were examined during continuous (CR) and interval (INT) running. In a repeated measures design, 10 subjects twice performed 30 min of CR at 70% of their peak treadmill velocity, followed by 10 bouts of INT at 100%. Between trial reliability of mean and amplitude changes in TOI and tHb during CR were determined. Muscle de-oxygenation and re-oxygenation rates during INT were calculated using 3 analytical methods; i) linear modelling, ii) minimum and maximum values during work/rest intervals, and iii) mean values during work/rest intervals. Reliability was assessed using coefficient of variation (CV; %). During CR, mean TOI was more reliable (3.5%) compared with TOI amplitude change (34.7%), while mean tHb (12%) was similar to both absolute (9.2%) and relative (10.2%) amplitude changes. During INT, de-oxygenation rates analysed via linear modelling produced the lowest CV (7.2%), while analysis using min-max values produced the lowest CV (9.3%) for re-oxygenation rates. In conclusion, while the variables demonstrated CVs lower than reported changes in training-induced adaptations and/or differences between athletes and controls (23– 450%), practitioners are encouraged to consider the advantages/disadvantages of each method when performing their analysis.
Keywords: reproducibility; time delay; near infrared spectroscopy; re-oxygenation rates; de-oxygenation rates